Task-oriented training in stroke rehabilitation: Qualitative study on perspectives and challenges among Pakistani physiotherapists - Ayesha Afridi; Arshad Nawaz Malik; Neha Raheel; Umme Aiman; Fajar Shahid; Aneeqa Iftikhar; Maryam Rehman (PLoS ONE, 2025)
Objective The aim of the study is to explore how Pakistani physiotherapists integrate Task Oriented Training (TOT) in stroke rehabilitation, categorizing its use across motor function, cognitive rehabilitation, and balance training, while identifying barriers and adaptation strategies. Methods A qualitative descriptive study was conducted using semi-structured interviews with 22 experienced physiotherapists. Data were analyzed using Braun and Clarke’s six-step thematic analysis, with ATLAS.ti9 for coding. Results Among the 22 participating physiotherapists, 18 (82%) reported incorporating TOT for motor and balance recovery, while only 8 (36%) emphasized cognitive rehabilitation due to training gaps and patient engagement challenges. Major barriers included resource limitations reported by 15 participants (68%), time constraints by 12 participants (55%), and cultural beliefs by 12 participants (55%), which therapists addressed through home-based modifications and caregiver involvement. Conclusion TOT is a valuable yet underutilized approach in Pakistani stroke rehabilitation, requiring standardized guidelines, cognitive rehabilitation training, and policy reforms to enhance effectiveness. Future research should focus on cost-effective, scalable rehabilitation models to improve stroke recovery outcomes in resource-limited settings.